Increased Lymphatic Vessel Length Is Associated With the Fibroblast Reticulum and Disease Severity in Usual Interstitial Pneumonia and Nonspecific Interstitial Pneumonia - Lara, Abigail R. (American College of Chest Physicians, 2012)
BACKGROUND: Lymphangiogenesis responds to tissue injury as a key component of normal wound healing. The development of fibrosis in the idiopathic interstitial pneumonias may result from abnormal wound healing in response to injury. We hypothesize that increased lymphatic vessel (LV) length, a marker of lymphangiogenesis, is associated with parenchymal components of the fibroblast reticulum (organizing collagen, fibrotic collagen, and fibroblast foci), and its extent correlates with disease severity. METHODS: We assessed stereologically the parenchymal structure of fibrotic lungs and its associated lymphatic network, which was highlighted immunohistochemically in age-matched samples of usual interstitial pneumonia (UIP), nonspecific interstitial pneumonia (NSIP) with FVC < 80%, COPD with a Global Initiative for Obstructive Lung Disease stage 0, and normal control lungs. RESULTS: LV length density, as opposed to vessel volume density, was found to be associated with organizing and fibrotic collagen density (P < .0001). Length density of LVs and the volume density of organizing and fibrotic collagen were significantly associated with severity of both % FVC (P < .001) and diffusing capacity of the lung for carbon monoxide (P < .001). CONCLUSIONS: Severity of disease in UIP and NSIP is associated with increased LV length and is strongly associated with components of the fibroblast reticulum, namely organizing and fibrotic collagen, which supports a pathogenic role of LVs in these two diseases. Furthermore, the absence of definable differences between UIP and NSIP suggests that LVs are a unifying mechanism for the development of fibrosis in these fibrotic lung diseases.